2012
DOI: 10.1128/iai.00295-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes That Contribute to the Pathogenesis of Invasive Pneumococcal Disease by In Vivo Transcriptomic Analysis

Abstract: ABSTRACTStreptococcus pneumoniae(the pneumococcus) continues to be responsible for a high level of global morbidity and mortality resulting from pneumonia, bacteremia, meningitis, and otitis media. Here we have used a novel technique involving niche-specific, genome-widein vivotranscriptomic analyses to identify genes up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 51 publications
4
68
0
1
Order By: Relevance
“…pneumoniae is a diverse and adaptable pathogen, capable of surviving in a range of niches within its human host. Previous studies from our laboratory have identified changes in in vivo transcriptional profile within a given strain that facilitate survival in distinct host niches (nasopharynx, lungs, blood, and brain) and/or aid progression from one niche to another (26,27,35,36). However, genetic differences between strains also result in pneumococci with inherent tropism for one niche over another.…”
Section: Discussionmentioning
confidence: 79%
“…pneumoniae is a diverse and adaptable pathogen, capable of surviving in a range of niches within its human host. Previous studies from our laboratory have identified changes in in vivo transcriptional profile within a given strain that facilitate survival in distinct host niches (nasopharynx, lungs, blood, and brain) and/or aid progression from one niche to another (26,27,35,36). However, genetic differences between strains also result in pneumococci with inherent tropism for one niche over another.…”
Section: Discussionmentioning
confidence: 79%
“…S. pneumoniae contains genes encoding at least 20 carbohydrate transporters in the core genome (66) and can ferment Ͼ30 different carbohydrates (67). Genes regulating carbohydrate metabolism, PTS, and ABC transporters have been identified as important during tissue-specific disease (29,68,69). Carbohydrate metabolism may provide selective advantages in different host niches, as the carbon source availability in the nasopharynx will be drastically different from other body sites.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae transcriptional profiles change in response to environmental stimuli and differ between the upper respiratory tract and other tissue sites (28,29). Understanding how transcriptional profiles are altered under various conditions will provide a critical step to understanding mechanisms that underlie progression from biofilm colonization to disease.…”
mentioning
confidence: 99%
“…Mutant and wild-type bacteria were grown separately in serum broth and then mixed at an input ratio of 1:1, and 50 l of bacterial suspension was used to challenge mice intranasally under anesthesia. Nasal wash, nasal tissue, lung, and blood samples were collected and processed as described previously (26,27). Each sample was serially diluted and plated on blood agar and on blood agar with erythromycin to determine the ratio of mutant to wild-type bacteria.…”
Section: Construction Of Mutantsmentioning
confidence: 99%